Occupational Hazards and Productivity of Poultry Farmers in Osun State of Nigeria - Ajetomobi, J.O.; Ajagbe, F.A.; Adewoye, J.O. (International Journal of Poultry Science, 2010)
This study examined the degree of occupational hazards among Osun state poultry farmers and how it affects their productivity. A structured questionnaire was designed to obtain relevant information from 70 poultry farm owners chosen through random sampling techniques. Descriptive statistics and a linear production function were employed to analyze the data. The results showed that youths were the major set of people in poultry business in the state. All the poultry farmers and farm workers in the study area were educated. Given multiple responses, about 93% of the farm owners experienced physical hazards while 91% were involved in accident at one point or the other. Those who complained of chemical hazards were found to be 86%. An increase in the expenditure on drugs will lead to a decline in net revenue of the poultry farmers per hectares.